2017
DOI: 10.21859/ijpn-05051
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Self-determination Skills on Optimistic Explanatory Style and Academic Identity of Primary Male Students with Learning Disabilities

Abstract: Introduction: This study aimed at examining the effects of teaching self-determination skills on the optimistic explanatory style and academic identity of primary male students with learning disabilities in Ahwaz city, Iran. Methods: The present study was a field experimental study with pre-test/post-test and follow-up. The sample consisted of 27 primary male students with learning disabilities who were enrolled in the academic year of 2013-2014. The participants were selected using the random sampling method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results of this research are in line with the results of the research, Research by Leon, Nunes and Lemon (2015), Abbasi andShahni Yilagh (1396), Brandenberg, Neuer andHascher (2018) and Frost (2007) but the results of this study were not in line with the results obtained from Farzan (2013) research. In general, it can be concluded that empowerment package training with selfdetermination approach can provide a very good platform for increasing performance and improving academic math beliefs of male and female students.…”
Section: Discussionsupporting
confidence: 64%
“…The results of this research are in line with the results of the research, Research by Leon, Nunes and Lemon (2015), Abbasi andShahni Yilagh (1396), Brandenberg, Neuer andHascher (2018) and Frost (2007) but the results of this study were not in line with the results obtained from Farzan (2013) research. In general, it can be concluded that empowerment package training with selfdetermination approach can provide a very good platform for increasing performance and improving academic math beliefs of male and female students.…”
Section: Discussionsupporting
confidence: 64%